On the role of caspase-recruitment domain proteins in apoptosis and NFkB activation - Bouchier-Hayes, Lisa (Trinity College (Dublin, Ireland). Department of Genetics, 2002)
Apoptosis and NFkB activation are two physiological processes that are essential for host mediated response to cellular injury. Apoptosis is a mechanism that removes damaged or unwanted cells. NFkB is a transcription factor that controls the expression of a number of cytokines and other mediators of inflammation. Recent studies have revealed that the molecular pathways that result in apoptosis or NFkB activation share a number of common elements. Pathways leading to apoptosis converge on the caspase cascade while pathways leading to NFkB activation converge on the IKK complex. Moreover, many of the steps in these pathways are controlled by a series of specific protein-protein interactions. A number of conserved protein modules such as the CARD and DED motifs mediate these interactions. To further characterise the role of CARD-containing proteins in apoptosis and NFkB actiyation this thesis focuses on the molecular characterisation of two CARD proteins CARDINAL and Nod1.
Keywords: Genetics, Ph.D.; Ph.D. Trinity College Dublin